Sanitation Marketing in Lao People's Democratic Republic - World Bank (Washington, DC, 2016)
This report summarizes the results, lessons and recommendations to the Government of Lao PDR from two Technical Assistance projects (TA) “Supporting Demand Creation for Sanitation through Community Led Total Sanitation” and “Sanitation Marketing in Lao PDR” carried out by the World Bank’s Water and Sanitation Program between October 2012 and December 2015. The development objective of the TAs was to increase improved sanitation and hygiene practices and change community behavior to achieve Open Defecation Free (ODF) status at the village level. This report documents the results and lessons learned from the TA program that includes experiences both from government-led rural sanitation service delivery within two provinces in Southern Lao PDR (Champasak and Sekong) , as well as from national-level engagement to strengthen systems, tools and capacity building approaches for scaling-up rural sanitation service delivery. The report makes recommendations to government on how - with the support of development partners – the effectiveness and scale of rural sanitation services can be increased to achieve sustainable sanitation outcomes for the rural population of Lao PDR. It also proposes recommendations for the engagement of the World Bank Water Practice in the sector in support of rural sanitation service delivery, aligned with lending operations,notably the Poverty Reduction Fund (PRF3) and the Health Governance and Nutrition Development Project (HGNDP). In addition a number of important learnings at implementation level are highlighted, so that operational processes can be improved to make last-mile delivery more effective and efficient.